Automated harvesting and processing of protein crystals through laser photoablation. Issue 4 (1st April 2016) - Zander, Ulrich; Hoffmann, Guillaume; Cornaciu, Irina; Marquette, Jean-Pierre; Papp, Gergely; Landret, Christophe; Seroul, Gaël; Sinoir, Jérémy; Röwer, Martin; Felisaz, Frank; Rodriguez-Puente, Sonia; Mariaule, Vincent; et al.
Abstract : New methods for crystal mounting, soaking and cryocooling contribute to bridging the automation gap between crystallization and X‐ray data collection. Abstract : Currently, macromolecular crystallography projects often require the use of highly automated facilities for crystallization and X‐ray data collection. However, crystal harvesting and processing largely depend on manual operations. Here, a series of new methods are presented based on the use of a low X‐ray‐background film as a crystallization support and a photoablation laser that enable the automation of major operations required for the preparation of crystals for X‐ray diffraction experiments. In this approach, the controlled removal of the mother liquor before crystal mounting simplifies the cryocooling process, in many cases eliminating the use of cryoprotectant agents, while crystal‐soaking experiments are performed through diffusion, precluding the need for repeated sample‐recovery and transfer operations. Moreover, the high‐precision laser enables new mounting strategies that are not accessible through other methods. This approach bridges an important gap in automation and can contribute to expanding the capabilities of modern macromolecular crystallography facilities.